Grand Vizier Kara Mustafa’s army towards the population of the attacked areas of Hungary and Austria during the Vienna Expedition of 1683 in the light of selected Ottoman sources - Wybranowski, Dariusz (Balcanica Posnaniensia. Acta et studia, 2024)
The aim of the article is to analyze the methods of the Ottoman army under the command of Grand Vizier Kara Mustafa and the Tatars supporting him against the people of the Hungarian and Lower Austrian areas during the Turkish expedition to Vienna in 1683. The primary sources are the accounts of chroniclers (Silahdar Mehmed aga of Fyndykla, Jebedji Hasan Esiri) and historians (Husein Hezarfenn, defterdar Sari Mehmed Pasha) of the Ottoman era. Important relations are included into the grand vizier's letters to the residents of the Hungarian city of Sopron and Vienna. These reports show that Ottoman forces sought to capture some cities and Vienna itself without a fight, counting on their surrender. They also succeeded in winning over some Hungarian magnates hostile to the Habsburgs (Imre Thököly, the Batthyanych and Draskovics families). However, terror was mainly used against the local population, which meant the extermination of prisoners of war - military (so-called „tongues”) and civilians, as well as the taking of women and children into slavery („jasyr”). Chroniclers report, among other things, cases of rewarding Ottoman soldiers and Tartars in exchange for supplied captives, who were later murdered. There are numerous reports on the destruction of occupied areas, mass looting and rape of women and boys. The attacked areas were almost completely destroyed and the population decimated. According to calculations, between 80,000 and more than 100,000 residents were killed or taken prisoner during these events.